Detecting Fraudulent Financial Reporting In State-Owned Company: Hexagon Theory Approach - Winwin Yadiati; Anhinta Rezwiandhari; Ramdany (Universitas Serang Raya, 2023)
This study aims to investigate the impact of the hexagonal fraud theory in the detection of fraud in the financial statements of state-owned enterprises (BUMN). This study is a quantitative approach whose data comes from the company's annual financial statements published by the Indonesia Stock Exchange (IDX) using multiple regression analysis techniques. The results of the study explain that simultaneously Financial Stability (Stimulus), External Pressure (Stimulus), Nature of Industry (Opportunity), Auditor Change (Capability), Change of Directors (Rationalization), Number of CEO Images (Arrogance), and Cooperation with Government Projects (Collusion) has a positive effect in detecting fraudulent financial statements of SOEs. Partially Financial Stability, External Pressure, Nature of Industry, Change of Directors, and Cooperation with Government Projects have a positive effect in detecting fraudulent financial statements of SOEs. Changes in Auditors and the Number of CEO Images have no effect in detecting fraudulent financial statements in BUMN for the 2012-2019 period. The results of this study can provide an overview of the factors that may cause fraudulent financial statements in SOEs. It is hoped that the results of this study can provide input to interested parties in strategic decisions.